Changes in Urine Microalbumin-to-Creatinine Ratio in Children with Sickle Cell Disease over Time - Shatat, Ibrahim F.; Qanungo, Suparna; Hudson, Shannon; Laken, Marilyn A.; Hailpern, Susan M. (Frontiers in Pediatrics, 2016)
Background: Approximately 20% of children with sickle cell disease (SCD) have microalbuminuria (MA). Very little is known about the progression of MA in children and young adults with SCD. Methods: In this study, we analyzed 5 year EMR data of 373 children (with ≥2 Microalbumin to creatinine (MA/Cr) ratio measurements) followed at the Medical University of South Carolina to determine the rate, direction, magnitude and predictors of MA/Cr change over time. Results: Age range was 1 – 22 years; mean 10.2 ± 5.2 years, 49.5% were male. Median follow up duration was 3.12 ±1.16 years. At baseline, 328 children had normal (<20 mg/L) MA level. Forty-five (12.1%) of children had MA (≥ 20 mg/L), of which 91% were ≥ 8 years and 21 (47%) continued to have MA at the end of the study period. On the other hand, during the study period, 24 new patients developed MA and 24 normalized their MA to levels <20 mg/L. In multivariate logistic regression model, age and bilirubin levels were predictive of MA/Cr increase in patients who received at least one blood transfusion during the study period. Baseline MA level was not predictive of the change in MA/Cr. Conclusions: In children and young adults, microalbuminuria is considered a marker of early renal injury. Over time, MA/Cr levels may increase or decrease. Further studies are needed to confirm our findings, assess the reliability of MA as marker of long-term renal injury and identify high risk patients likely to have worsening of MA over time.